Structures and solid solution mechanisms of pyrochlore phases in the systems Bi2O3-ZnO-(Nb, Ta)2O5 - Tan, Kar Ban; Khaw, Chwin Chieh; Lee, Chnoong Kheng; Zainal, Zulkarnain; Miles, Gabrielle (Elsevier, 2010)
The crystal structures of two pyrochlore phases have been determined by Rietveld refinement of combined X-ray and neutron powder diffraction data. These are stoichiometric, Bi1.5 ZnTa1.5O7 and non-stoichiometric Bi1.56Zn0.92Nb1.44O6.86. In both structures, Zn is distributed over A- and B-sites; Bi and Zn are displaced off-centre, to different 96g A-site positions; of the three sets of oxygen positions, O(1) are full, O(2) contain vacancies and O(3) contain a small number of oxygen, again in both cases. Comparisons between these structures, those of related Sb analogues and literature reports are made.